2004
DOI: 10.1119/1.1748074
|View full text |Cite
|
Sign up to set email alerts
|

What do students really learn from interactive multimedia? A physics case study

Abstract: Interactive multimedia is promoted as an effective and stimulating medium for learning science, but students do not always interact with multimedia as intended by the designers. We discuss students’ interactions with an interactive multimedia program segment about projectile motion in the context of long jumping. Qualitative data were collected using a video camera and split-screen recorder to record each student’s image, voice, and student–program interactions. Left to themselves, students’ interactions were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 20 publications
0
20
0
2
Order By: Relevance
“…Los modos didácticos de emplear los vídeos en la enseñanza de la física y sus diversos efectos en el aprendizaje que logran los estudiantes se han investigado ampliamente (Zollman y Fuller 1994, Beichner 1996, Rodrigues et al 2001, Yeo et al 2004, Kearney 2004, Climent 2009, Martínez et al 2012. La mayoría de los resultados indican que la interacción de los estudiantes con los vídeos beneficia la comprensión de los conceptos y las leyes de física.…”
Section: El Uso De Vídeo En La Enseñanza Y El Aprendizaje De La Físicaunclassified
“…Los modos didácticos de emplear los vídeos en la enseñanza de la física y sus diversos efectos en el aprendizaje que logran los estudiantes se han investigado ampliamente (Zollman y Fuller 1994, Beichner 1996, Rodrigues et al 2001, Yeo et al 2004, Kearney 2004, Climent 2009, Martínez et al 2012. La mayoría de los resultados indican que la interacción de los estudiantes con los vídeos beneficia la comprensión de los conceptos y las leyes de física.…”
Section: El Uso De Vídeo En La Enseñanza Y El Aprendizaje De La Físicaunclassified
“…According to these authors, the use of simulated experience on the projectiles motion made the students interact superficially since they kept their intuitive representations on the motion which are erroneous. In the same perspective, Zhou, Brouwer, Nocente and Martin [26] showed that it is possible to create the conceptual change while resorting to experiences that will be followed by a discussion initiated by the teacher where students will argue their ideas following the simulations. But for that to happen, the teacher must have the necessary expertise to manage the erroneous representations of the students.…”
Section: IImentioning
confidence: 99%
“…Manske and Conati 6 suggest that little evidence exists to show that games can trigger learning, unless they are supported by other activities. Disconcertingly, Yeo, et al 7 showed that interactive multimedia experiences may not illuminate the key physics concepts for their students, despite interactivity and animated graphics. In their study, "only following researcher intervention, did students develop awareness" of the abstract physics concepts.…”
Section: Etop 2009mentioning
confidence: 99%